Implementasi Pendidikan Karakter dalam Upaya Peningkatan Mutu Lulusan di SMK Negeri 8 Bandar Lampung - Fitri Yaningsih; Hendri Dunan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The main problem in education today is the suboptimal implementation of character education in schools, particularly at the Vocational High School (SMK) level. This has resulted in low graduate quality, particularly in terms of attitudes, behavior, and work readiness. Various forms of student behavioral deviations indicate that character education has not been managed systematically and sustainably. This study aims to describe the implementation of character education to improve graduate quality at SMKN 8 Bandar Lampung. This study used a qualitative approach with a descriptive research type. Data collection techniques were conducted through observation, interviews, and documentation studies involving the principal, teachers, and related parties. Data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation techniques. The research results indicate that the implementation of character education at SMKN 8 Bandar Lampung has been carried out through the planning, implementation, and supervision stages, but has not been optimal. Obstacles identified include weak program organization, unclear task allocation, and suboptimal supervision. Nevertheless, character education has contributed positively to improving the quality of graduates, particularly in fostering discipline, responsibility, work ethic, and religious behavior in students. Therefore, strengthening the management of character education in an integrated and sustainable manner is necessary to improve the quality of graduates who have character and are ready to face the world of work.